Effect of Baicalein on the Pharmacokinetics of Cilostazol and Its Two Metabolites in Rat Plasma Using UPLC-MS/MS Method - Weng, Qinghua; Chen, Chaojie; Xiong, Jianhua; Liu, Ya-Nan; Pan, Xinxin; Cui, Ju; Cai, Jian-Ping; Xu, Ren-Ai (Frontiers in Pharmacology, 2022)
This study aimed to explore the effect of baicalein on the pharmacokinetics of cilostazol (CLZ) and its two metabolites 3,4-dehydro cilostazol (3,4-CLZ) and 4′-trans-hydroxy cilostazol (4′-CLZ) in rats using a newly established ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) method. Ticagrelor was used as an internal standard (IS), then cilostazol and its two metabolites were separated by means of a UPLC BEH C18 column (2.1 mm × 50 mm, 1.7 μm) using gradient elution method with 0.4 mL/min of flow rate. Acetonitrile as organic phase and water with 0.1% formic acid as aqueous phase constructed the mobile phase. Selective reaction monitoring (SRM) mode and positive ion mode were preferentially chosen to detect the analytes. Twelve SD rats were divided into two groups (n = 6) when CLZ was administered orally (10 mg/kg) with or without oral baicalein (80 mg/kg). The selectivity, linearity, recovery, accuracy, precision, matrix effect and stability of UPLC-MS/MS assay were satisfied with the standards of United States Food and Drug Administration guidelines. In control group, AUC0-∞ and Cmax of CLZ were 2169.5 ± 363.1 ng/mL•h and 258.9 ± 82.6 μg/mL, respectively. The corresponding results were 3767.6 ± 1049.8 ng/mL•h and 308.6 ± 87.9 for 3, 4-CLZ, 728.8 ± 189.9 ng/mL•h and 100.3 ± 51.3 μg/mL for 4′-CLZ , respectively. After combination with baicalein, AUC0-∞ and Cmax of CLZ were 1.48, 1.38 times higher than the controls. Additionally, AUC0-∞ and Cmax were separately decreased by 36.12 % and 19.54 % for 3,4-CLZ, 13.11 % and 44.37 % for 4′-CLZ. Baicalein obviously alters the pharmacokinetic parameters of CLZ, 3,4-CLZ and 4′-CLZ in rats. These results suggested that there was a potential drug-drug interaction between baicalein and CLZ. Therefore, it must raise the awareness when concomitant use of CLZ with baicalein, the dosage regimen of CLZ should be taken into consideration, if this result is confirmed in clinical studies.